Brain Amide Proton Transfer Imaging of Rat With Alzheimer’s Disease Using Saturation With Frequency Alternating RF Irradiation Method - Wang, Runrun; Chen, Peidong; Shen, Zhiwei; Lin, Guisen; Xiao, Gang; Dai, Zhuozhi; Zhang, Bingna; Chen, Yuanfeng; Lai, Lihua; Zong, Xiaodan; Li, Yan; Tang, Yanyan; et al. (Frontiers in Aging Neuroscience, 2019)
Amyloid-β (Aβ) deposits and some proteins play some essential roles in AD pathogenesis. Amide proton transfer (APT) imaging as an indicator of tissue protein has shown promise for AD diseases. In this study, we chose 20 AD model rats as the experimental group and 20 sham-operated rats as the control group. They were firstly underwent Y-maze test, and then performed on a 7.0 T animal MRI scanner to acquire brain amide proton transfer image using saturation with frequency alternating RF irradiation (APTSAFARI) method. Compared with the control group, APT (3.5ppm) values of brain were significantly reduced in AD models (p<0.002). The APTSAFARI imaging is more significantly than APT imaging (p<0.0001). The Y-maze showed there were loss spatial learning and memory in the AD model, as well as significant neuronal loss in the hippocampus CA1 region and cortex compared with sham-operated rat. In conclusion, we demonstrated that APT technology could potentially provide molecular biomarkers for the noninvasive diagnosis of AD. These results suggested that APTSAFARI MRI could be used as an effective tool to improve the accuracy of diagnosis of AD as a possible biomarker.